2018
DOI: 10.1186/s12958-018-0331-4
|View full text |Cite
|
Sign up to set email alerts
|

Circulating osteopontin and its association with liver fat content in non-obese women with polycystic ovary syndrome: a case control study

Abstract: BackgroundOsteopontin (OPN) plays an important role in inflammatory processes and insulin resistance. Polycystic ovary syndrome (PCOS) is a reproductive metabolic disease associated with insulin resistance and metabolic abnormalities, including high levels of liver fat content (LFC). The objective of this study was to explore whether circulating OPN independently contributes to elevated LFC in non-obese PCOS patients.MethodsThis study included 61 non-obese PCOS patients and 56 age-matched healthy women from Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Serum osteopontin levels were determined by the sandwich ELISA method (Elabscience, Catalog number: E-EL-H1347, USA). The intra-assay CV and the inter-assay CVS were < 4.1% and < 6.7% (15).…”
Section: Laboratory Investigationsmentioning
confidence: 83%
See 3 more Smart Citations
“…Serum osteopontin levels were determined by the sandwich ELISA method (Elabscience, Catalog number: E-EL-H1347, USA). The intra-assay CV and the inter-assay CVS were < 4.1% and < 6.7% (15).…”
Section: Laboratory Investigationsmentioning
confidence: 83%
“…Following the overnight fasting, we obtained blood samples from each patient in Groups PCOS and Control in the morning during the second or third day of their menstrual cycle for laboratory investigations, including glucose, cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglyceride, insulin, the glycated hemoglobin (HbA1c), C-reactive protein (CRP), follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), prolactin, total testosterone, and thyroid stimulating hormone (TSH). We calculated the homeostasis assessment insulin resistance index (HOMA-IR) using fasting serum insulin and fasting plasma glucose as described (15). The triglyceride/glucose index was calculated with the relevant measurements for each patient (20).…”
Section: Laboratory Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In relation to macrophage infiltration and inflammation, OPN is also demonstrated to associate in the pathogenesis of atherosclerotic process, insulin resistance, and malignant disorders [19]. Recently only a few studies have indicated that increased osteopontin levels may be associated with PCOS in selected populations [14,21].…”
Section: Evaluation and Measurementsmentioning
confidence: 99%